Pengaruh Dukungan Organisasi dan Kontrol Diri Terhadap Disiplin Kerja Karyawan di PT. X di Kabupaten Sleman - Rezha Fata (LPPM Universitas Proklamasi 45, 2020)
This study aims to determine: (1) the effects of organizational support to employees work discipline, (2) the effects of self-control on employees work discipline, (3) the effects of organizational support and self-control to employees work discipline at PT. X. This research uses quantitative methods. Sample in this study were 60 employees, who were determined using the product moment. Measuring instruments used organizational support scale, self-control scale, and work discipline scale. Analysis technique for testing the hypothesis uses multiple regression techniques.The results showed that: (1) there was a significant influence between organizational support on employee work discipline at PT. X as evidenced by a significance value of 0.001 (p <0.05), (2) there is a significant influence between self-control on employee work discipline at PT. X as evidenced by the significance value of 0.000 (p <0.05), (3) the simultaneous and significant influence between organizational support and self-control on employee work discipline at PT. X as evidenced by the F value of 22.941 with a significance of 0.000 (p <0.05).